Nanostructured Porous Silicon Photonic Crystal for Applications in the Infrared - G. Recio-Sánchez; V. Torres-Costa; M. Manso-Silván; R. J. Martín-Palma (Journal of Nanotechnology)
In the last decades great interest has been devoted to photonic crystals aiming at the creation of novel devices which can control light propagation. In the present work, two-dimensional (2D) and three-dimensional (3D) devices based on nanostructured porous silicon have been fabricated. 2D devices consist of a square mesh of 2 μm wide porous silicon veins, leaving 5×5 μm square air holes. 3D structures share the same design although multilayer porous silicon veins are used instead, providing an additional degree of modulation. These devices are fabricated from porous silicon single layers (for 2D structures) or multilayers (for 3D structures), opening air holes in them by means of 1 KeV argon ion bombardment through the appropriate copper grids. For 2D structures, a complete photonic band gap for TE polarization is found in the thermal infrared range. For 3D structures, there are no complete band gaps, although several new partial gaps do exist in different high-symmetry directions. The simulation results suggest that these structures are very promising candidates for the development of low-cost photonic devices for their use in the thermal infrared range.